Growth And Lipid Accumulation of Chaetoceros calcitrans After Phosphorus And Light Intensity Optimization - Rizal Maulana Hasby; Ismi Farah Syarifah; Opik Taufiqurrohman (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2023)
AbstractGrowth and lipid content of Chaetoceros calcitrans are greatly influenced by environmental factors. The aims of this study to optimize phosphorus concentrations and light intensity on the growth and lipid accumulation of C. calcitrans. This study used N:P:light intensity concentration from the previous research, namely 441:36.2 µM:2,500 lux (12:1:2,500 lux). Concentrations of P were then optimized to 36.2 µM, 27.5 µM, 18.1 µM, 9.05 µM (1; 0.75; 0.5; 0.25) and light intensity to 2,500; 3,000; 3,500; 4,000 lux. C. calcitrans was cultured in medium f/2 guillard, the initial density was 6 x 105 cells/mL. Sampling for lipid analysis was conducted in exponential, stationary, and the end of stationary phase by centrifugation, whereas lipid was extracted using the Bligh and Dyer method, and dried lipids were analyzed using gas chromatography-GC. The highest lipid content found at the late stationary phase of the N:P concentrations and light intensity 12:0.5:(4,000 lux), there was 15.46 ± 0.53%-dw with the highest cell density of 5.5 ± 5.56 x 106 cells/mL. The analysis result showed that palmitoleic acid (C16:1) was the highest fatty acid produced by each optimization. Nutritional deficiency and high light intensity were triggers for of C. calcitrans to accumulate lipids, and influence the fatty acid profile of C. calcitrans.AbstrakPertumbuhan dan kandungan lipid Chaetoceros calcitrans sangat dipengaruhi oleh faktor lingkungan. Tujuan penelitian ini adalah untuk mengoptimasi konsentrasi fosfor dan intensitas cahaya terhadap pertumbuhan dan akumulasi lipid C. calcitrans. Penelitian ini menggunakan hasil konsentrasi N:P:intensitas cahaya dari penelitian sebelumnya, yaitu 441:36.2µM:2,500 lux (12:1:2,500 lux). Konsentrasi P kemudian dioptimasi menjadi 36,2 µM, 27,5 µM, 18,1 µM, 9,05 µM (1; 0,75; 0,5; 0,25), dan intensitas cahaya menjadi 2.500; 3.000; 3.500; 4.000 lux. C. calcitrans dikultur dalam medium f/2 guilard, densitas awal 6 x 105 sel/mL. Pengambilan sampel untuk analisis lipid dilakukan pada fase eksponensial, stasioner, dan akhir stasioner dengan sentrifugasi, sedangkan lipid diekstraksi menggunakan metode Bligh dan Dyer, lipid kering dianalisis menggunakan kromatografi gas-GC. Kandungan lipid tertinggi terdapat pada fase akhir stasioner konsentrasi N:P dan intensitas cahaya 12:0,5:(4,000 lux), yaitu sebesar 15,46 ± 0,53%-dw dengan kerapatan sel tertinggi 5,5 ± 5,56 x 106 sel/mL. Hasil analisis menunjukkan bahwa asam palmitoleat (C16:1) merupakan asam lemak tertinggi yang dihasilkan oleh masing-masing optimasi. Kekurangan nutrisi dan intensitas cahaya yang tinggi menjadi pemicu C. calcitrans. mengakumulasi lipid, dan mempengaruhi profil asam lemak C. calcitrans.